Fluid mechanics : - Çengel, Yunus A. (Singapore McGraw-Hill Education, 2014)
Fluid Mechanics is intended for use in Fluid Mechanics courses found in Civil and Environmental, General Engineering, and Engineering Technology and Industrial Management departments. It is also serves as a suitable reference and introduction to Fluid Mechanics principles.